2019
DOI: 10.1097/qad.0000000000002040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incident hepatitis C infection on CD4+ cell count and HIV RNA trajectories based on a multinational HIV seroconversion cohort

Abstract: Background: Most studies on hepatitis C virus (HCV)/HIV co-infection do not account for the order and duration of these two infections. We aimed to assess the effect of incident HCV infection, and its timing relative to HIV seroconversion (HIVsc) in HIV-positive men who have sex with men (MSM) on their subsequent CD4 T-cell count (CD4) and HIV-RNA viral load (VL) trajectories. Methods:We included MSM with well-estimated dates of HIVsc from 17 cohorts within the CASCADE Collaboration. HCV co-infected MSM were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…There are two possible reasons: HIV infection biologically increases the risk of HCV infection [ 38 ], and HIV is more easily transmitted by sexual contact than HCV [ 39 ]. Furthermore, HIV infection often precedes HCV infection in MSM [ 39 , 40 ]. Therefore, many HCV antibody‐positive participants at the time of HIV diagnosis likely acquired HCV following HIV infection and before HIV diagnosis, possibly related to a long period of high‐risk behaviour, that increases the risk of HCV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two possible reasons: HIV infection biologically increases the risk of HCV infection [ 38 ], and HIV is more easily transmitted by sexual contact than HCV [ 39 ]. Furthermore, HIV infection often precedes HCV infection in MSM [ 39 , 40 ]. Therefore, many HCV antibody‐positive participants at the time of HIV diagnosis likely acquired HCV following HIV infection and before HIV diagnosis, possibly related to a long period of high‐risk behaviour, that increases the risk of HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption partly explains the association between HCV antibody positivity and late HIV diagnosis. Another possible explanation is that HCV co‐infection may affect the CD4 count, which decreases after HCV seroconversion in PLWH compared with PLWH only [ 40 ]. However, the effect of HCV co‐infection on reduced CD4 count is transient [ 36 ], and HCV serostatus does not affect HIV disease progression [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of rates of CD4 decline have shown that various factors can influence the speed of decline. For example co-infection with HCV can increase the rate of decline of CD4 cells, [38] and CD4 counts may vary between different geographic areas with faster CD4 decline observed in Asia compared to Europe [39].…”
Section: Discussionmentioning
confidence: 99%
“…Fifty‐six studies fulfilled the inclusion criteria, as shown in Table 1 , comprising a total of 309203 MSM PLHIV. Switzerland contributed five studies, 18 , 20 , 37 , 38 , 39 United States had 11 studies, 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 Spain had four studies, 51 , 52 , 53 , 54 Netherlands had four studies, 55 , 56 , 57 , 58 three studies were from France, 17 , 59 , 60 six studies were from Taiwan, 22 , 61 , 62 , 63 , 64 , 65 eight studies were from United Kingdom, 19 , 21 , 23 , 25 , 66 , 67 , 68 , 69 two studies were from Europe, 70 , 71 two studies from Japan, 24 , 72 two studies from Australia. 73 , 74 One study each were from Belgium, 75 …”
Section: Resultsmentioning
confidence: 99%